2017
DOI: 10.1021/acsami.7b01404
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluoric Acid-Free Electroless Deposition of Metals on Silicon in Ionic Liquids and Its Enhanced Performance in Lithium Storage

Abstract: Metal nanoparticles such as Au, Ag, Pt, and so forth have been deposited on silicon by electroless deposition in the presence of hydrofluoric acid (HF) for applications such as oxygen reduction reaction, surface-enhanced Raman spectroscopy, as well as for lithium ion batteries. Here, we show an HF-free process wherein metals such as Sb and Ag could be deposited onto electrodeposited silicon in ionic liquids. We further show that, compared to electrodeposited silicon, Sb-modified Si demonstrates a better perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[56] Lahiri et al show electrodeless deposition of metals on Si without HF in ionic liquids and use in situ AFM to observe the process of layer-by-layer growth of metals on Si. [57]…”
Section: Siliconmentioning
confidence: 99%
“…[56] Lahiri et al show electrodeless deposition of metals on Si without HF in ionic liquids and use in situ AFM to observe the process of layer-by-layer growth of metals on Si. [57]…”
Section: Siliconmentioning
confidence: 99%
“…Therefore, ionic liquids have attracted much attention as electrolyte solvents for use in LIBs. Some researchers reported negative‐electrode performance of electrodeposited Si electrode in lithium bis(trifluoromethanesulfonyl)amide/1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethanesulfonyl)amide, which was relatively high cycling stability compared to that in an organic electrolyte . We previously investigated the electrochemical performance of Si‐based electrodes in various ionic liquid electrolytes .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported negative-electrode performance of electrodeposited Si electrode in lithium bis(trifluoromethanesulfonyl)amide/1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)amide, which was relatively high cycling stability compared to that in an organic electrolyte. [10][11][12] We previously investigated the electrochemical performance of Si-based electrodes in various ionic liquid electrolytes. [13][14][15][16][17][18] We found that the cycling stabilities of Si-alone electrodes were significantly improved in some ionic liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, formation of GaSb nanowires was shown to be possible using electroless deposition. As the open circuit potential of Sb/Sb 3+ is more positive compared to Si and Ge in the same ionic liquid, Sb modification of both electrodeposited Si and Ge was achieved (Lahiri et al, 2016, 2017). The electroless deposition of Sb on Ge from 0.1 M SbCl 3 -[Py 1, 4 ]TFSA led to the formation of Sb nanoparticles.…”
Section: Electroless Deposition Of Alloys and Composite Materialsmentioning
confidence: 99%
“…It is evident that modifying the Ge with Sb led to a higher Na capacity storage even at higher current densities of 0.83 A g −1 compared to Ge which was cycled at a current density of 0.54 A g −1 . Similar to the modification of Ge with Sb, electrodeposited silicon was also modified by Ag and Sb as it was found that the open circuit potentials of both Ag/Ag + and Sb/Sb 3+ are more positive to Si(IV)/Si in the ionic liquid (Lahiri et al, 2017). From quartz crystal microbalance (QCM) measurements, the rate of deposition for Sb on Si was found to be 2.7 ng sec −1 for the first 1,000 s which then decreases to 0.4 ng sec −1 .…”
Section: Electroless Deposition Of Alloys and Composite Materialsmentioning
confidence: 99%